INVESTIGATING MODULATION OF SPECIFIC GENE EXPRESSION IN IN VITRO DIFFERENTIATION OF HUMAN UMBILICAL CORD BLOOD DERIVED MESENCHYMAL STEM CELL INTO INSULIN SECRETING CELL - Phúc, Phạm Văn (Vietnam Journal of Biotechnology, 2011)
Mesenchymal stem cells (MSCs) are multipotent cells that may serve as a source of cells for generation of surrogate P cell which can apply to treat diabetes. However, effect of diabetic treatment by stem cell transplantation remains low, especially by mesenchymal stem cell transplantation. It is supposed that there are some errors in transdifferentiation process from mesenchymal stem cells into nsulin secreting cells. TTiis work investigated expression of ten genes in the gene profile related with differentiation process from pancreatic stem cells into beta cells. Mesenchymal stem cells are derived from human umbilical cord blood. They are cultured and differentiated into osteogenic and adipogenic to examine their differential capacity. Then they are transdifferentiated into insulin secreting cells by three steps protocol: the first, treating in H-DMEM medium supplement with FBS and retinoic acid; the second, treating in L-DMEM supplement with BS, nicotinamide and EGF; the last, treating in L-DMEM supplement FBS and exendin^. In each step of this protocol, differentiated cells are investigated via examination of expression of ten genes by RT- PCR method. The gene profile of transdifferentiated cells are compared to that of beta cells in vivo. The results showed that mesenchymal stem cells expressed two genes: nestin, Isl-1 when they were not induced. After inducing with some chemicals, insulin secreting cells expressed 10 genes: nestin, Isl-1, Pdx-1, Ngn3, Pax6, Pax4, Nkx2.2, Nkx6.1, Glut-2, Insulin; while beta cells express nestin 7 genes: Nestin, Pdx-1, Nkx2.2, Nkx6.1, Pax6, Glut-2 and Insulin. Difference in specific gene expression modulation was identified between in vitro trans-differentiation and in vivo differentiation. That means islets derived from in vitro trans-differentiation were not fully indentical to islets derived.